Physicochemical Properties of Porang Nanocoating with the Addition of Essential Oils - Suriati; Rudianta; Ngakan Putu Gede Satria Kesumayasa (SEAS (Sustainable Environment Agricultural Science), 2023)
Porang nanocoating is a food coating that has the potential to be developed and is gaining popularity among the public to extend the shelf life of fruits and vegetables. Porang Nanocoating is a nano-sized edible coating made from porang tuber glucomannan. The addition of essential oils can improve the property of the nanocoating of people as a natural antimicrobial coating. Thyme, cinnamaldehyde and eugenol essential oils are known to have excellent antimicrobial properties. Antimicrobial ability is strongly influenced by the concentration of added essential oil. The purpose of this study was to determine the effect of the type and concentration of essential oils on the physicochemical properties of porang nanocoating. This study used a factorial completely randomized design (CRD) with two factors, namely the type of essential oil treatment including essential oils of thyme, eugenol, cinnamaldehyde. While other treatments are essential oil concentrations, namely 1%, 2%, and 3%. The results of this study indicate that the type of essential oil and its concentration affect the physicochemical properties of the porang nanocoating. The physicochemical properties of porang nanocoating based on the type of essential oil treatment gave the following average values: viscosity 16.67 m.Pa.s. – 17.50 m.Pa.s; degree of acidity (pH) range 6.29 – 6.33; color 13.50 – 13.95; transparency 89.40 – 89.56; has stable emulsion properties or there is no separation of the emulsion and in the microscopic test the oil droplets or bubbles are few While other treatments are essential oil concentrations, namely 1%, 2%, and 3%. The results of this study indicate that the type of essential oil and its concentration affect the physicochemical properties of the porang nanocoating. The physicochemical properties of porang nanocoating based on the type of essential oil treatment gave the following average values: viscosity 16.67 m.Pa.s. – 17.50 m.Pa.s; degree of acidity (pH) range 6.29 – 6.33; color 13.50 – 13.95; transparency 89.40 – 89.56; has stable emulsion properties or there is no separation of the emulsion and in the microscopic test the oil droplets or bubbles are few While other treatments are essential oil concentrations, namely 1%, 2%, and 3%. The results of this study indicate that the type of essential oil and its concentration affect the physicochemical properties of the porang nanocoating. The physicochemical properties of porang nanocoating based on the type of essential oil treatment gave the following average values: viscosity 16.67 m.Pa.s. – 17.50 m.Pa.s; degree of acidity (pH) range 6.29 – 6.33; color 13.50 – 13.95; transparency 89.40 – 89.56; has stable emulsion properties or there is no separation of the emulsion and in the microscopic test the oil droplets or bubbles are few The physicochemical properties of porang nanocoating based on the type of essential oil treatment gave the following average values: viscosity 16.67 m.Pa.s. – 17.50 m.Pa.s; degree of acidity (pH) range 6.29 – 6.33; color 13.50 – 13.95; transparency 89.40 – 89.56; has stable emulsion properties or there is no separation of the emulsion and in the microscopic test the oil droplets or bubbles are few The physicochemical properties of porang nanocoating based on the type of essential oil treatment gave the following average values: viscosity 16.67 m.Pa.s. – 17.50 m.Pa.s; degree of acidity (pH) range 6.29 – 6.33; color 13.50 – 13.95; transparency 89.40 – 89.56; has stable emulsion properties or there is no separation of the emulsion and in the microscopic test the oil droplets or bubbles are few. Treatment of essential oil concentrations gives physicochemical properties to Porang Nanocoating which has an average Viscosity value of 16.11 m.Pa.s. – 18.61 m.Pa.s; The degree of acidity (pH) ranges from 6.25 to 6.39; Color 12.80 – 14.91; Transparency 89.39 – 89.52; has stable properties or does not occur emulsion separation in the stability test and in the microscopic test has few oil droplets or bubbles.